2013
DOI: 10.1097/ta.0b013e31829e2543
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival and neurologic outcomes in children with traumatic out-of-hospital cardiac arrest during the early postresuscitative period

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…29 Neurological clinical evaluation appears to be the main diagnostic tool when dealing with the probability of brain damage after cardiac arrest. This has been previously stated in other studies, [30][31][32][33] reflecting the difficulty of managing these patients after such a critical life-threatening event. Our results state that there is no common protocol that deals with managing these patients, trying to assess their outcome and establishing their follow-up.…”
Section: Discussionmentioning
confidence: 71%
“…29 Neurological clinical evaluation appears to be the main diagnostic tool when dealing with the probability of brain damage after cardiac arrest. This has been previously stated in other studies, [30][31][32][33] reflecting the difficulty of managing these patients after such a critical life-threatening event. Our results state that there is no common protocol that deals with managing these patients, trying to assess their outcome and establishing their follow-up.…”
Section: Discussionmentioning
confidence: 71%
“…Significant heterogeneity (I-squared value 0.87) did not support pooling the data from these 3 studies (Topjian 97 : OR, 0.62; 95% CI, 0.41-0.93; Lin 98 : OR, 0.10; 95% CI, 0.03-0.32; and Lin 99 : OR, 0.07; 95% CI, 0.02-0.25). For the important outcome of harm to patient, we identified no evidence.…”
Section: Consensus On Sciencementioning
confidence: 95%
“…For the important outcome of survival to hospital discharge, we identified very-low-quality evidence from 3 pediatric observational studies of IHCA and OHCA (downgraded for risk of bias, inconsistency, indirectness, and imprecision) [97][98][99] involving a total of 615 subjects, showing worse outcomes when children experienced hypotension after ROSC. Significant heterogeneity (I-squared value 0.87) did not support pooling the data from these 3 studies (Topjian 97 : OR, 0.62; 95% CI, 0.41-0.93; Lin 98 : OR, 0.10; 95% CI, 0.03-0.32; and Lin 99 : OR, 0.07; 95% CI, 0.02-0.25).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…survival to hospital discharge with good neurological outcome (RR 0.78; 95% CI 0.62-0.99). Two other paediatric observational studies (102,103) of IHCA and OHCA involving a total of 615 children showed worse outcomes (survival to hospital discharge) in patients who experienced hypotension after ROSC. There was significant heterogeneity (I-squared value 0.87), which does not support pooling of data from the aforementioned studies (Topjian: OR 0.62; 95% CI 0.41-0.93; Lin: OR 0.10; 95% CI 0.03-0.32; and Lin: OR 0.07; 95% CI 0.02-0.25).…”
Section: (C) Post-rosc Fluid and Inotrope Therapymentioning
confidence: 99%